Incremento de potássio em plantas de girassol helianthus annuus l. submetidas ao estresse salino - Lopes, Monique Cristina Simao (2015)
Sunflower (Helianthus annuus L.) is an oleaginous that has its growth and productive potential affected by nutritional disorders induced by the high saline stress. The action of the ions Na+ e Cl – compromise enzimes and membranes, beyond decreasing the capacity of potassium absorption an essential component for the cellular osmotic adjustment and the stomatal condutance. Knowing the importance of the oleaginous and potassium with relation to development of plants in saline ambiences, this task had like objective evaluating the influence of K+ increment in two cultivars of sunflowers submitted to saline stress, through an analysis on growing indicators hydric status and a possible contribution of organic and inorganic solutes in osmotic adjustment of sunflowers. Seedlings of two sunflower cultivars (Catissol 01 and Hélio 253) were submitted to saline stress simulated by sodium chloride (NaCl) and to supply of K+ to saline solution, on hydroponic cultivation for 10 days in a greenhouse. The experimental delineation was entirely randomised, using three treatments (Control, Salt and Salt + K) and eleven repetitions. It was determined the absolute growth rate (TCA), relative growth rate (TCR), leaf area ratio (RAF), leaf weight ratio (RPF), root weight ratio (RPR), relation of the aerial part with the root system (RAPRS), relative water content (CRA), percentage of moisture (U), electrolytes leakage (VE), content of ions Na+ e K+, content of total soluble sugars (AST), total free amino acids (AALT), total soluble proteins (PST) and proline (PRO). Salinity affected the plants growth, causing a reduction on TCA, TCR, RAF and RPF, such as on CRA in the leaves of both cultivars, being the effect of NaCl more expressive in Catissol 01. In the roots and independent of cultivars, CRA and the U were not affected by salinity. The imposition of saline stress caused a significant increase on VE in both cultivars, being the damage in the cellular membranes intenser in Catissol 01. The increment of K+ to saline solution interfered only the VE, causing contrary effect in the cultivars. The presence of NaCl promoted a bigger accumulation of ions Na+ in both cultivars, being more expressive in Catissol 01. Additionally, it was the cultivation that presented a better response to the increment of K+ to saline solution (S+K). The contents of AST and AALT in Catissol 01 decreased while PST and PRO increased with salinity, with relation to the control. Already in the Hélio 253 there was a decrease of AST and a increase of AALT. The increment of K+ to saline solution (S + K) promoted increases in AST and AALT accumulation in Catissol 01, and an increase in Hélio 253 PST and PRO 253, with respect to saline treatment. The obtained results indicate that the treatments with NaCl were capable of inducing alterations on growing parameters, as well on the content of inorganic and organic solutes of both cultivars. Catissol 01 and Hélio 253 respond of a diferentiated form to the effects of salinity and to the supply of K+ with relation to the accumulation of inorganic and organic solutes, showing that the response of plants to cultivate and is dose dependent. Hélio 253 is more efficient on the accumulation of Na+, because it ensures its development in saline environment without being affected by ion toxicity. Although the accumulation of AST, AALT, PST and PRO, are related to the osmotic adjustment, it is possible that the accumulation of these solutes have occurred due to disorders promoted by salinity